Gold(III) meets azulene: a class of [(tBuC∧N∧C)AuIII(azulenyl)] Pincer complexes - Eppel, Daniel; Oberhof, Nils; Dietl, Martin C.; Cieslik, Patrick; Rudolph, Matthias; Eberle, Lukas; Krämer, Petra; Stuck, Fabian; Rominger, Frank; Dreuw, Andreas; Hashmi, A. Stephen K. (Organometallics, 2021)
A synthetic route to new gold(III) complexes was developed. From a [(tBuC∧N∧C)AuCl] complex as a precursor, a substitution by different azulene moieties was achieved. Because of the extraordinary photophysical properties of both substituted [(C∧N∧C)Au] compounds and azulene building blocks, the fusion of these generated organometallic azulene/gold(III) pincer hybrids. The isolated complexes were fully characterized and investigated, including X-ray single-crystal structure analysis, the electrochemical properties, and UV-vis spectra.
Gesehen am 20.01.2022